Organizational Culture, Distributional Justice, And Procedural Justice - Nasruji Nasruji; Debiyanti Kune; Fitri Devi Lestari Izaak; Ade Risna Sari; Abdul Manap (Pusat Riset dan Inovasi Nasional, 2023)
The aim of this study is to investigate the relationships between organizational culture, distributive justice, and procedural justice. Employees at Armor Kopi Bandung made up the study's target group, and incidental sampling was used for the sampling process. The study makes the following assumptions: there is employee churn; employee absenteeism varies; and some employees work part-time. 92 respondents completed a questionnaire to gather information, which was then examined using multiple linear regression analysis. The study's conclusions show that organizational culture, distributive justice, and procedural justice all significantly and favorably influenced organizational commitment. The findings have implications for business executives by assessing factors including organizational culture, distributive justice, and procedural justice, all of which are still low as indicated in the discussion section. This will help to encourage increased organizational commitment.